A proposed single-phase five-level PFC rectifier for smart grid applications: an experimental evaluation - Monteiro, Vítor Duarte Fernandes (2019)
The use of PFC rectifiers has assumed an increasingly preponderance, contributing in a decisive way to improve the power quality indices, since they allow to operate with sinusoidal current on the ac side and with controlled voltage on the dc side. In this paper is proposed a novel PFC rectifier that allows five levels of voltage. As noted in the paper, it presents a number of interesting advantages when compared to the conventional five level PFC rectifier, mainly because it requires less passive and active semiconductors to produce the different voltage levels and requires less hardware resources to implement the gate driver circuits. The proposed five level PFC (5L PFC) rectifier operates in boost mode and has a single dc link (although with a midpoint to achieve the various levels), being an important feature for applications in smart grids (e.g., smart electrical appliances and electric mobility chargers). The key topics of the 5L PFC rectifier are addressed and discussed based on the analysis of the principle of operation. As current control strategy it was adopted the model predictive control. Experimental results in steady and transient state were considered for an effective validation of the 5L PFC rectifier, verifying the operation with: sinusoidal current on the ac side; multi level operation with five levels; controlled dc link voltage.